Financial Literacy and Saving Behavior among Factory Workers: The Mediating Role of Self-Control - Ayu Wulandari; Lilik Nur Cholidah; Moh Muklis Sulaeman (Journal of Business Innovation and Accounting Research, 2026)
Purpose - This study examines whether financial literacy is associated with saving behavior among factory workers in Lamongan, Indonesia, and whether self-control mediates this association. Design/methodology/approach - A cross-sectional survey was conducted with 91 factory workers. Financial literacy, self-control, and saving behavior were each operationalized as reflective constructs with eight indicators. The proposed model was estimated using partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4. Findings - Financial literacy was positively associated with saving behavior (beta = .414, t = 4.329, p < .001) and self-control (beta = .781, t = 19.284, p < .001). Self-control was also positively associated with saving behavior (beta = .518, t = 4.840, p < .001). The indirect association between financial literacy and saving behavior through self-control was significant (beta = .404, t = 4.255, p < .001), indicating complementary partial mediation. The model explained 77.3% of the variance in saving behavior and 61.0% of the variance in self-control. Research limitations/implications - Because the data are cross-sectional, self-reported, and geographically concentrated, the estimates should be interpreted as associations rather than causal effects. Longitudinal or experimental designs using objective financial outcomes are required to establish temporal and causal ordering. Practical implications - Workplace financial programs may be more effective when financial education is combined with behavioral supports that strengthen goal setting, expenditure control, and regular saving routines. Originality/value - The study extends research on the financial knowledge-behavior gap by positioning self-control as a behavioral mechanism linking financial literacy to saving behavior among factory workers, a population rarely examined in this literature.